Limitations of proof of stake algorithm in blockchain: A review - Shifferaw, Yenatfanta; Lemma , Surafel (Zede Journal of Ethiopian Engineers and Architects, 2023)
Blockchain is a new technology that has emerged to provide solutions to various sectors including health, insurance, advertising and many more. Despite the benefits, the technology has its own challenges with respect to the architecture and the consensus protocols involved. Proof of stake (PoS) is one type of consensus protocol by which a decision is made in order to handle transactions inside the blockchain technology. PoS concept states that a person can mine or validate block transactions according to how many coins the person holds. This work is aimed at studying the pros and cons of PoS and its proposed variations, and come up with recommendations to handle the drawbacks that currently exist in these algorithms. A detailed exploration has been carried out to understand the issues behind proof of stake protocol and the consensus algorithms that tried to address those issues. Consequently, four research gaps were identified. These gaps are less decentralized blockchain, vulnerable to 51% attack, not tested for security and performance, and problem of another issue being raised when trying to solve one. Most of the previously developed algorithms are based on proposing variation to the PoS working principle and trying to handle a particular limitation of PoS. Through careful analysis, specific and assumed best options on how to go about in addressing each of the four research gaps are laid down as future directions. This includes bringing hybrid implementation of different capability based consensus algorithms; generating, maintaining and testing traceability links on the system frequently; implementing merged mining of capability based consensus algorithm on a blockchain with a higher hash rate and through bringing more participants to the platform and making the committee of participant's mobility dynamic.